2013
DOI: 10.1002/bit.24884
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing cellulase activity

Abstract: Commercial exploitation of lignocellulose for biotechnological production of fuels and commodity chemicals requires efficient-usually enzymatic-saccharification of the highly recalcitrant insoluble substrate. A key characteristic of cellulose conversion is that the actual hydrolysis of the polysaccharide chains is intrinsically entangled with physical disruption of substrate morphology and structure. This "substrate deconstruction" by cellulase activity is a slow, yet markedly dynamic process that occurs at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 143 publications
(259 reference statements)
0
56
0
1
Order By: Relevance
“…High resolution imaging techniques such as electron microscopy and scanning probe microscopy are widely used to study cellulose structure (Bubner et al 2013). These techniques can provide nanoscale information about cellulose structure, but lack chemical specificity, thus revealing mostly topographic details of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution imaging techniques such as electron microscopy and scanning probe microscopy are widely used to study cellulose structure (Bubner et al 2013). These techniques can provide nanoscale information about cellulose structure, but lack chemical specificity, thus revealing mostly topographic details of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, most of the published work deals with exoglucanases, particularly celobiohydrolase I (CBHI) acting on pure cellulose substrates. A comprehensive review including important contributions to the area can be found in (Bubner et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Whole pretreated biomass has a complex architecture across multiple length scales, and while this architecture has been studied extensively for many different substrates (Antal 1985;Ciesielski et al 2014;Donohoe and Resch 2015), only in rare cases have structural effects of enzymatic degradation of these substrates been reported (Resch et al 2014). In contrast numerous studies on enzyme induced changes to the morphology of pure cellulose substrates like BMCC ribbons, Valonia fibrils and Avicel have been published over the years (for an extensive review see Bubner et al 2013). The general observation is that cellobiohydrolases (CBHs)-notably CBH1-target crystalline regions while endoglucanases (EGs) target amorphous regions, and that the combined action of the two types of enzymes has a profoundly different effect than each of them alone (Bubner et al 2013;Payne et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…In contrast numerous studies on enzyme induced changes to the morphology of pure cellulose substrates like BMCC ribbons, Valonia fibrils and Avicel have been published over the years (for an extensive review see Bubner et al 2013). The general observation is that cellobiohydrolases (CBHs)-notably CBH1-target crystalline regions while endoglucanases (EGs) target amorphous regions, and that the combined action of the two types of enzymes has a profoundly different effect than each of them alone (Bubner et al 2013;Payne et al 2015). Furthermore it has been found that CBHs degrades cellulose fibrils from the ends and cause narrowing and sharpening of the fibril while EGs have no apparent spatial preference and cause general surface disruption or fibrillation (Chanzy and Henrissat 1985;Chanzy et al 1983).…”
Section: Introductionmentioning
confidence: 99%